(untitled) (Historia, 2021)
Foreign Policy in Post-Apartheid South Africa: Security, Diplomacy and Trade, addresses the urgent need for a comprehensive examination of South Africa’s post-apartheid foreign policy. Complementing recent scholarship on South Africa’s foreign policy, this volume differs in its historical, geographical and thematic comprehensiveness and demonstrates that South Africa’s foreign policy is shaped by its domestic context, particularly overcoming the legacies of apartheid.